Islamic Moral Value of self-reliance: A Drive for Poverty Alleviation and Entrepreneurship amongst Women in Kontagora Emirate, Nigeria - Yusuf, Hauwa'u Talatu (UIN Walisongo Semarang, 2021)
The Islamic moral value of self-reliance is a value system that has been emphasized in numerous Ayat of the Glorious Qur’an and Ahadith of the Prophet (SAW). Kontagora Emirate consists of six local government areas with diverse cultural values and different languages, but with the majority of its population being Muslims and women. This paper seeks to look into the moral obligation in the conduct of business or trade by women in Islam and the conditions to be observed by Muslim women during vocations. It also aims to find out how they acquire the entrepreneurial skills; the duration taken to learn a particular skill and the types of businesses, trades, vocations etc. What impact does it have on the Muslim woman’s status economically, socially, educationally, politically? In order to achieve the above objectives, the paper adopts the survey method complimented with interview. The findings of the paper are that most Muslim women in Kontagora Emirate engage in one form of trade/vocation or the other through self help efforts such as Adashi and mini-women self help efforts kungiya. The paper concludes that with the help of Government and non-governmental/private individual’s assistance the women in Kontagora Emirate will achieve more and contribute more to economic growth of the Emirate and the state at large.